2015
DOI: 10.2135/cropsci2014.09.0633
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Misclassification Rates in Identification of Haploid Seeds from Induction Crosses in Maize with High‐Oil Inducers

Abstract: In vivo production of double haploid (DH) lines in maize (Zea mays L.) requires reliable identification of haploid (H) seeds. A new method for achieving this goal is production of induction crosses with high‐oil (HO) inducers and sorting the resulting H and diploid crossing (C) seeds based on their oil content (OC). Balancing the false discovery rate (FDR) and false negative rate (FNR) by choice of a suitable proportion α of selected seeds represents an unsolved problem with this method. We investigated soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In addition, it has been previously noted that use of R1‐nj has resulted in a high number of false positives (true diploids among putative haploids) (Röber et al, 2005; Prigge et al, 2011; Choe et al, 2012; Melchinger et al, 2014). It is also possible that all haploids present in the induction cross could not be detected based on R1‐nj marker expression and can also be falsely included among the diploids (Melchinger et al, 2015b). Röber et al (2005) showed that temperate flint germplasm with high FDR also have high FNR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been previously noted that use of R1‐nj has resulted in a high number of false positives (true diploids among putative haploids) (Röber et al, 2005; Prigge et al, 2011; Choe et al, 2012; Melchinger et al, 2014). It is also possible that all haploids present in the induction cross could not be detected based on R1‐nj marker expression and can also be falsely included among the diploids (Melchinger et al, 2015b). Röber et al (2005) showed that temperate flint germplasm with high FDR also have high FNR.…”
Section: Discussionmentioning
confidence: 99%
“…Two non‐anthocyanin based alternatives were proposed for haploid identification to address the above‐mentioned limitations of the R1‐nj marker. Pollination with haploid inducers with sufficiently high kernel oil content, followed by rapid differentiation of haploid kernels based on their lower oil content using Nuclear Magnetic Resonance Spectroscopy (NMR), has been previously demonstrated (Melchinger et al, 2013, 2015b). This method facilitates high‐throughput identification of haploids through automation.…”
mentioning
confidence: 99%
“…DH plants are very important in the integration of physical and genetic maps and thus allow the accurate detection of candidate genes of interest [124,125]. The R1-nj (Navajo) anthocyanin colour marker has been successfully applied for the identification of haploids [126]. Similarly, SSR and SNP markers have been applied to detect DH and genotypes of isogenic lines and hybrids [127][128][129].…”
Section: Identification Of Haploid/diploid Plants and Cultivars Genotmentioning
confidence: 99%
“…In all three experiments described below, D 0 seeds always refer to putative haploid seeds, selected from induction crosses with (a) inducers RWS, UH400 or RWS×UH400, using visual classification based on expression of the R1‐nj embryo marker (Molenaar & Melchinger, ) or (b) high‐oil inducer UH600×UH601, using the oil content of seeds (Melchinger et al, ). This selected fraction of seeds besides true haploid seeds always contains a certain fraction of false positives, i.e., C seeds that were wrongly classified as haploid (Melchinger et al, ). In all three experiments, the source germplasm and the inducers were taken from the UHOH maize breeding programme (see Table S1 for overview of experiments, induction crosses and method for identification of putative haploid seeds).…”
Section: Methodsmentioning
confidence: 99%
“…However, the misclassification rates associated with this marker system can be quite substantial (≥30%) depending on the germplasm (Chaikam, Martinez, Melchinger, Schipprack, & Boddupalli, ; Prigge et al, ) or classification may even be impossible due to inhibitory genes such as C1‐I present in some source germplasm (Chaikam et al, ; Paz‐Ares, Ghosal, & Saedler, ). Development of inducers equipped with the red root marker (Chaikam et al, ) or high oil content of the seed (Melchinger, Schipprack, Würschum, Chen, & Technow, ) and sorting of seeds from induction crosses based on their oil content (Melchinger, Böhm et al, ; Melchinger, Munder et al, ) help to reduce the misclassification rates (Melchinger et al, ), but undesirable C seeds (=false positives) can still occur at considerable rates, depending on the source germplasm and inducer. As a result, varying proportions of C seeds are planted in the field after chromosome doubling and must be rogued later in the nursery.…”
Section: Introductionmentioning
confidence: 99%